Liberation day : stories - Saunders, George, 1958- (Random House, 2022)
"The 'best short story writer in English' (Time) is back with a masterful collection that explores ideas of power, ethics, and justice, and cuts to the very heart of what it means to live in community with our fellow humans. With his trademark prose--wickedly funny, unsentimental, and perfectly tuned--Saunders continues to challenge and surprise: here is a collection of prismatic, deeply resonant stories that encompass joy and despair, oppression and revolution, bizarre fantasy and brutal reality. 'Love Letter' is a tender missive from grandfather to grandson, in the midst of a dystopian political situation in the not-too-distant future, that reminds us of our obligations to our ideals, ourselves, and each other. 'Ghoul' is set in a Hell-themed section of an underground amusement park in Colorado, and follows the exploits of a lonely, morally complex character named Brian, who comes to question everything he takes for granted about his 'reality.' In 'Mother's Day,' two women who loved the same man come to an existential reckoning in the middle of a hailstorm. And in 'Elliott Spencer,' our eighty-nine-year-old protagonist finds himself brainwashed--his memory 'scraped'--a victim of a scheme in which poor, vulnerable people are reprogrammed and deployed as political protesters. Together, these nine subversive, profound, and essential stories coalesce into a case for viewing the world with the same generosity and clear-eyed attention as Saunders does, even in the most absurd of circumstances"--